Thyroid function abnormalities in individuals with sickle cell disease: a meta-analysis - Sagad O. O. Mohamed; Hussein Ahmed; Mohammed A. H. Mohammednoor; Khalefa B. K. Alzubeir; Safaa Fadlelmoula; Osman O. A. Abdallah; Izzut Awad Ahmed (Thyroid Research)
Abstract Background There has been an increasing comprehension and recognition of endocrine dysfunction among both pediatric and adult patients with sickle cell disease (SCD). Thyroid disorders can have significant clinical consequences, including growth retardation and impaired cognitive function. However, there is a disparity in the available data concerning the magnitude and spectrum of thyroid abnormalities in this population. This review aimed to provide a systematic summary and analyses on the status of thyroid function abnormalities in individuals with SCD. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive search was conducted across Medline/PubMed, Google Scholar, World Health Organization Virtual Health Library Regional Portal, and ScienceDirect. Pooled prevalence and standardized mean difference (SMD) estimates with 95% confidence intervals (CIs) were calculated using Comprehensive Meta-Analysis Software version 3.3. Results Nineteen studies met the inclusion criteria and were incorporated into the analyses. Serum thyroid-stimulating hormone (TSH) levels were significantly higher in SCD patients compared to controls (SMD = 1.184; 95% CI, 0.269–2.099; p = 0.011). While non-significant, there was a trend towards lower levels of triiodothyronine (T3), thyroxin (T4), free T3, and free T4 in the SCD group (T3: SMD = -1.746; 95% CI, -3.561–0.070; p = 0.059; T4: SMD = -1.365; 95% CI, -3.030–0.300; p = 0.108; free T3: SMD = -0.384; 95% CI, -1.128–0.356; p = 0.311; free T4: SMD = -1.205; 95% CI, -2.522–0.111; p = 0.073). The pooled prevalence of hypothyroidism and subclinical hypothyroidism among SCD patients was found to be 4.9% and 8.7%, respectively. Conclusion Individuals with SCD exhibit a tendency towards elevated TSH levels compared to the general population, with a subset potentially developing thyroid abnormalities, particularly subclinical hypothyroidism. Although not highly prevalent in the SCD population, monitoring thyroid function remains essential due to the potential for progression to overt hypothyroidism and its associated adverse health outcomes.